PELAKSANAAN STANDARISASI PEMBERIAN PATEN DALAM INVENSI BIDANG OBAT-OBATAN DI INDONESIA - Abdul Kadir Jaelani; Alexander A. Kurniawan; Lusia Indrastuti (Legality : Jurnal Ilmiah Hukum, 2019)
This research is motivated by a patent given to Sanofi Pasteur, a French citizen who acts as a patent holder for Japanese encephalitis vaccine, measles, mumps, rubella using a pig enzyme in the form of trypsin as a catalyst in the process of making vaccines, whereas Article 9 letter a of Law Number 13 Year 2016 regarding Patents states that inventions that cannot be granted a Patent include processes or products that are announced, used or implemented in contravention of statutory regulations, religion, public order or decency. The purpose of this study is to analyze the standardization of the provision of patents in the field of medicine. This type of research is normative law. The data of this study are secondary data. Analysis of the data used is descriptive analytic. The research concludes that first, the background of the formation of the provisions of an invention that is considered to be contrary to religion in Indonesia as regulated in Article 9 letter a of the Law of the Republic of Indonesia Number 13 of 2016 is based on several justifications namely justification based on Article 27.2 and Article. 27.3 TRIPs Agreement and justification based on the translation of the Pancasila as the ideology of the Indonesian people, especially the Precepts of Godhead. Secondly, the provisions of an invention that is considered to be contrary to the religion of Islam in the field of medicines that contain illicit elements cannot be implemented because the provisions of Article 9 letter a of Law Number 13 Year 2016 are universal.